1998
DOI: 10.1080/07315724.1998.10718810
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Resistant Starches on Fecal Bulk, Short Chain Fatty Acids, Blood Lipids and Glycemic Index

Abstract: The potential physiological benefits of the resistant starches studied appear to relate to colonic health in terms of effects on fecal bulk and SCFA metabolism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
126
2
13

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 215 publications
(148 citation statements)
references
References 47 publications
7
126
2
13
Order By: Relevance
“…Conceivably, the values of H 2 at 3·5 h post-food intake may represent the true baseline level of breath H 2 . In addition, we continued to test breath H 2 for 16 h, which was longer than 12 h commonly used (38,41) , because the levels of breath H 2 12 h after the RS rice meal were still higher than that of control with WT rice. This longer effect of the RS rice intake on the production of H 2 may be because of unique genetic background of Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…Conceivably, the values of H 2 at 3·5 h post-food intake may represent the true baseline level of breath H 2 . In addition, we continued to test breath H 2 for 16 h, which was longer than 12 h commonly used (38,41) , because the levels of breath H 2 12 h after the RS rice meal were still higher than that of control with WT rice. This longer effect of the RS rice intake on the production of H 2 may be because of unique genetic background of Chinese.…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies on the relationship between the amount of available starch and blood glu cose response has shown a general inverse relationship between blood glucose response and indigestible starch (18)(19)(20)(21). However, at least two other studies reported that glycemic control was not affected with S in their human subjects (14,22). The principle purpose of the present study was to investigate the effect of resistant starch on blood lipid concentrations, and glucose and insulin responses in overweight subjects.…”
mentioning
confidence: 95%
“…Beneficial effects include improving the glycemic control in diabetes (Fontvieille et al, 1992;Wolever et al, 1992), reductions in blood insulin (Jenkins et al, 1998;Behall et al, 1989;Behall & Howe, 1995) or lipids (Behall et al, 1989;Jenkins et al, 1987), and potential decrease in the risk for development of diabetes (Salmeró n et al, 1997a,b). Hyperinsulinemia, an indication of insulin resistance, is one indicator of potentially developing non-insulin-dependent diabetes mellitus (NIDDM, Haffner et al, 1990).…”
Section: Introductionmentioning
confidence: 99%